The monkey and the dove : and four other true stories of animal friendships - Holland, Jennifer S. (Unlikely friendships for kids, 2012)
Presents five stories about animals who have forged unlikely, abiding bonds with other animals of different species, from the rhesus monkey and the white dove to the lion and the baby oryx.